Implication of the satellite cell in dystrophic muscle fibrosis: a self-perpetuating mechanism of collagen overproduction. - Alexakis, C; Partridge, T; Bou-Gharios, G (2007)
Because of its mechanical function, skeletal muscle is heavily influenced by the composition of its extracellular matrix (ECM). Fibrosis generated by chronic damage, such as occurs in muscular dystrophies, is thus particularly disastrous in this tissue. Here, we examined the interrelationship between the muscle satellite cell and the production of collagen type I, a major component of fibrotic ECM, by using both C2C12, a satellite cell-derived cell line, and primary muscle satellite cells. In C2C12 cells, we found that expression of collagen type I mRNA decreases substantially during skeletal muscle differentiation. On a single-cell level, collagen type I and myogenin became mutually exclusive after 3 days in differentiation medium, whereas addition of collagen markedly suppressed differentiation of C2C12 cells. Primary cultures of satellite cells associated with isolated single fibers of the young (4 wk old) mdx dystrophic mouse and of C57BL/10ScSn wild-type controls expressed collagen type I and type III mRNA and protein. This pattern persisted in wild-type mice at all ages. But, curiously, in older (18-mo-old) mdx mice, although the myogenic cells continued to express type III collagen, type I expression became restricted to nonmyogenic cells. These cells typically constituted part of a cellular sheet surrounding the old mdx fibers. This combination of features strongly suggests that the progression to fibrosis in dystrophic muscle involves changes in the mechanisms controlling matrix production, which generates positive feedback that results in a reprogramming of myoblasts to a profibrotic function.